Brain metastasis from gallbladder neuroendocrine carcinoma. Issue 11 (30th November 2020) - Sasaki, Hanako; Goto, Takayoshi; Hirao, Motohiro; Fujimoto, Yasunori
Abstract : A 52-year-old woman was diagnosed with unresectable gallbladder neuroendocrine carcinoma (GB-NEC) exhibiting lymph node and peritoneal metastases, and received eight courses of chemotherapy with irinotecan plus cisplatin. Radiological examinations revealed significant regression of the GB tumour and disappearance of metastatic lesions, so the patient underwent laparoscopic cholecystectomy. However, the patient presented with multiple haemorrhagic brain metastases (BMs) and died 13 months after the initial diagnosis despite neurosurgical interventions. Pathological examination of the resected gallbladder demonstrated an extensive fibrous scar along with tubular adenocarcinoma components, which may indicate that the chemotherapy eliminated a pre-existing neuroendocrine carcinoma (NEC) component. Furthermore, pathological analysis confirmed that the BMs comprised NEC. In patients with advanced GB-NEC, conversion surgery may be a reasonable option if a first-line chemotherapy leads to downstaging of the tumour. Second-line drug therapy and systemic screening might also be considered in cases with BMs.